Levoglucosan as a specific marker of fire events in Greenland snow - NATALIE KEHRWALD; ROBERTA ZANGRANDO; PAOLO GABRIELLI; JEAN LUC JAFFREZO; CLAUDE BOUTRON; BARBANTE, Carlo; GAMBARO, Andrea (Tellus B: Chemical and Physical Meteorology, 2012)
We demonstrate the use of levoglucosan (1,6-anhydro- d-D-glucopyranose) as a source-specific proxy of past fire activity in snow pits and ice cores. Levoglucosan is unambiguously a degradation product derived from cellulose burning at temperatures greater than 300 °C and is widely used as a biomass burning marker in aerosol analyses. We analyse samples collected from a 3 m snow pit at Summit, Greenland (72°20'N, 38°45'W; 3270 m a.s.l.), with a known depositional history where biomass burning aerosols were traced from their source in a Canadian smoke plume, through their eastward transport and deposition on the Greenland ice sheet, and their eventual burial by accumulating snow layers. The snow pit levoglucosan profile replicates oxalate concentrations from a known forest fire event, suggesting the applicability of levoglucosan as a marker of past fire activity in snow and by extension in ice cores. However, levoglucosan concentration peaks in the snow pit differ from those of ammonium and potassium, which are traditionally used as biomass burning proxies in snow and ice studies but which incorporate sources other than fire activity. The source specificity of levoglucosan can help determine the past relative contribution of biomass burning aerosols when used in conjunction with other proxies in snow and ice.